Applying Justice Theory to Service Recovery and its Influence on Customer Loyalty: Evidence from Online Food Delivery Services in the Philippines - Catian, Angelica D.; Fabular, Danny Boy T.; Garcia, Grace Zel; Parcia, Heidie Amor A.; Alonzo, Albert A.; Degoma, Junaisah Nissi L.; Palmes, Karem A. (International Review of Management and Marketing, 2026)
This study examines the effects of service recovery dimensions—distributive, procedural, and interactional justice—on customer loyalty among users of online food delivery (OFD) services in Iligan City, Philippines. It aims to determine which dimensions of perceived fairness most strongly influence post-recovery loyalty, thereby validating the applicability of Justice Theory in the digital service context. Despite the growing popularity of OFD platforms, recurring service failures such as delayed, incorrect, or missing orders continue to undermine customer satisfaction and loyalty. However, limited empirical evidence explores how fairness-based recovery strategies affect customer loyalty within emerging markets like the Philippines. A quantitative, descriptive–correlational research design was employed, utilizing a structured questionnaire administered to 200 OFD users who had experienced service failures and subsequent recovery. Statistical analyses, including correlation and multiple regression, were used to evaluate the predictive influence of each justice dimension on customer loyalty. Results revealed that distributive justice and interactional justice significantly predict customer loyalty, whereas procedural justice exerts no substantial effect. The model demonstrated strong explanatory power, indicating that fairness perceptions account for nearly half of the variance in loyalty behaviour. These findings affirm Justice Theory’s assertion that fairness perceptions are central to post-recovery satisfaction and loyalty formation. Practically, the study highlights the importance of empathetic communication and equitable compensation in sustaining customer relationships. Service recovery protocols that integrate tangible fairness with humane treatment can strengthen customer trust, enhance loyalty, and ensure the long-term success of online food delivery platforms.